SIKAP PETANI PADI ORGANIK TERHADAP PROGRAM OVOP (ONE VILLAGE ONE PRODUCT) BERBASIS KOPERASI PRODUK BERAS ORGANIK - Sendy Chistina Kusumawardhani; Bekti Wahyu Utami; Widiyanto Widiyanto (AGRITEXTS: Journal of Agricultural Extension, 2016)
This research aims to examines the factors forming attitudes of the farmer, it examines  the  attitudes   of  farmers  toward  OVOP  Program,  and  examines  the correlation between the factors forming attitudes with the attitudes of farmers toward OVOP  Program  in  Karanganyar Regency.  This research was carried out by using a descriptive method. The research location is determined purposively. The sampling technique   is   proportional   random   sampling   with   40   respondents   from   two cooperations are KKT Tani Makaryo and KSU Anugerah Jaya. Method of analysis used to determine the correlation of the factors forming attitudes with the attitudes of farmers toward OVOP Program is the correlation coefficient of Rank Spearman. Result of the research indicate that other’s influence factor have a very significant correlation. Farming experience, formal education, and non formal education have a significant correlation. Age, mass media, cultural of nature conservation and income don’t have a significant correlation.